Acute Manifestations of Neuromuscular Disease - Edmundson, Christyn; Bird, Shawn J. (Seminars in Neurology, 2019)
Neuromuscular emergencies may be defined as disorders or exacerbation of diseases of the peripheral nervous system that are rapidly progressive and potentially life-threatening. Such disorders can affect any level of the peripheral nervous system, from the muscle to the anterior horn cell. While their clinical manifestations may vary, severe morbidity and mortality is most frequently the result of neuromuscular respiratory failure. Some disorders, such as Guillain–Barré syndrome, provide the additional threat of severe, and potentially irreversible, nerve loss. Others, such as rhabdomyolysis and malignant hyperthermia, may produce serious medical complications. This article reviews neuromuscular emergencies by localization in the peripheral nervous system of the underlying disorder, as well as the identification and management of neuromuscular respiratory failure.
Keywords: neuromuscular emergencies; myasthenia gravis; Guillain–Barré syndrome; tetanus; botulism